Bibliometric and visual analysis of cerebral revascularization from 1999 to 2022 - Zhang, Ding; Li, Xiaoqian; Jia, Ni; Chen, Wei; Hu, Yueqiang (Frontiers in Neuroscience, 2023)
Background Cerebral revascularization is a neurosurgical procedure used to restore the cerebral collateral circulation channel. This study examines the countries, institutions, authors, journals, keywords, and references related to the disease in the field of cerebral revascularization from 1999 to 2022 from a bibliometrics perspective, evaluates the changes of knowledge structure clustering and identifies the new hot spots and new research directions in this field. Methods The Web of Science Core Collection (WOSCC) database and the PICOS retrieval method were used to conduct a comprehensive search for articles and reviews pertaining to cerebral revascularization. The final filtered data were bibliometrically and visually drawn using Microsoft office 365, CiteSpace (v.6.1.R2), and VOSviewer (v.1.6.18). Results From 1999 to 2022, a total of 854 articles pertaining to cerebral revascularization, which originated from 46 nations, 482 institutions, and 686 researchers, were extracted from the WOSCC database, and the number of publications in this field of study was rising. The United States held the highest proportion in the ranking analysis of countries, institutions, authors, and journals. By analyzing co-citations, the scientific organization of this field and the development status of frontier fields were realized. Cerebral revascularization, moyamoya disease, extracranial intracranial bypass, and occlusion are the current research focal points in the field of cerebral revascularization. Hyperperfusion and vascular disorder may also become a new study focus in this discipline in the near future. Conclusion Using the method of bibliometrics, this study analyzed and reviewed the articles in the field of cerebral revascularization, which enabled scholars to better comprehend the dynamic process in this field and provided a foundation for future in-depth research.